PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN IBU TENTANG IMUNISASI DASAR LENGKAP PADA BAYI DI WILAYAH KERJA PUSKESMAS JONGAYA - Khalida Ziah Sibualamu; Rosalina Hilda Murnihati; Sri Resky Mustafa; Evi Kusmayanti (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2023)
Background: Complete primary immunization is an important infectious disease prevention program for infants. The main obstacle to the success of infant immunization is the low level of awareness of mothers in bringing their babies to be immunized. This can be influenced by the lack of knowledge of mothers regarding the importance of primary immunization in infants, for this reason, education is needed. This study aimed to determine whether health education affects mothers' knowledge about complete primary immunization for infants. Design: This study used a quantitative and pre-experimental design (one group pretest-posttest design). The sample size in this study was 64 people, with the technique sampling purposive sampling. The intervention given in this study was health education using leaflet media. The instrument in this study used a questionnaire. The data in this study were analyzed using Wilcoxon Signed Rank Test. Results: There was a significant difference in knowledge (positive rating) before and after being given health education about complete primary immunization for infants (p<0.001). Conclusion: There was an effect of health education on mother's knowledge about complete primary immunization for infants. Suggestion: There is still a need for further series of studies with other methods and variables